2016
DOI: 10.1126/scisignal.aaf7694
|View full text |Cite
|
Sign up to set email alerts
|

Chemical proteomic map of dimethyl fumarate–sensitive cysteines in primary human T cells

Abstract: Dimethyl fumarate (DMF) is an electrophilic drug that is used to treat autoimmune conditions, including multiple sclerosis and psoriasis. The mechanism of action of DMF is unclear, but may involve the covalent modification of proteins or DMF serving as a pro-drug that is converted to monomethyl fumarate (MMF). Here, we found that DMF, but not MMF, blocked the activation of primary human and mouse T cells. Using a quantitative, site-specific chemical proteomic platform, we determined the DMF-sensitivity of > 24… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
130
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 149 publications
(141 citation statements)
references
References 72 publications
9
130
1
Order By: Relevance
“…Taken together, these results support the hypothesis that in addition to MMF, DMF can also directly contribute to the anti‐inflammatory and regenerative effects of this DMT. These results align with recent findings that have been previously observed in peripheral immune cells9, 10, 15 and brain‐resident microglia 9, 16…”
Section: Introductionsupporting
confidence: 93%
See 1 more Smart Citation
“…Taken together, these results support the hypothesis that in addition to MMF, DMF can also directly contribute to the anti‐inflammatory and regenerative effects of this DMT. These results align with recent findings that have been previously observed in peripheral immune cells9, 10, 15 and brain‐resident microglia 9, 16…”
Section: Introductionsupporting
confidence: 93%
“…Furthermore, it has been demonstrated that the anti‐inflammatory effects of fumarates may be restricted to DMF, with other fumarate metabolites having little influence on inflammation 9, 10, 13, 14. A recent report has demonstrated that DMF, but not metabolite monomethyl fumarate (MMF), is a potent inhibitor of NF‐ κ B signaling within immune cells through the modification in cysteine residues 15. This is consistent with findings that DMF promotes an anti‐inflammatory shift in activated microglia 9, 16.…”
Section: Introductionsupporting
confidence: 65%
“…We also believe that our studies, despite having uncovered more than 100 lysines targeted by fragment electrophiles, almost certainly still underestimate the global ligandability of lysines in the human proteome. The development and evaluation of larger compound libraries displaying more diversified recognition and amine-reactive elements, including covalent-reversible electrophiles (e.g., aldehydes), in combination with surveying complementary cell types (e.g., primary immune cells 62 , metabolic organs 63 ), should greatly enrich our understanding of functional and ligandable lysines in the human proteome and, through doing so, extend its druggable landscape for basic and translational research objectives…”
Section: Discussionmentioning
confidence: 99%
“…Thus, DMF may interact with cysteine residues in several proteins that regulate NF-kB signaling (Blewett et al, 2016). In addition, DMF inhibits ubiquitin-conjugating enzymes and thus prevents the degradation of the IkB repressor of NF-kB in response to IL-1b or Toll-like receptor agonists (McGuire et al, 2016).…”
Section: A Electrophilic Nuclear Factor (Erythroid-derived 2)-like 2mentioning
confidence: 99%
“…In addition, DMF inhibits ubiquitin-conjugating enzymes and thus prevents the degradation of the IkB repressor of NF-kB in response to IL-1b or Toll-like receptor agonists (McGuire et al, 2016). Moreover, DMF binds directly to specific cysteine residues in protein kinase C-u, a key kinase involved in signaling by the T cell receptor (Blewett et al, 2016). In addition, MMF and DMF activate the hydroxycarboxylic acid receptor-2, resulting in inhibition of NF-kB and downregulation of proinflammatory cytokines and adhesion molecules Gillard et al, 2015) and leading to decreased neutrophil infiltration .…”
Section: A Electrophilic Nuclear Factor (Erythroid-derived 2)-like 2mentioning
confidence: 99%